Success at Work, Life Patterns, and Overall Life Satisfaction: Changes in the Lives of Men and Women since the 1980s in West Germany - Angelika Tölke (Vierteljahrshefte zur Wirtschaftsforschung, 2001)
This paper focuses on the structural relationship between family building and upward mobility. Typically this relationship is analyzed for women only, while we include men as well. With new patterns of intimate partnerships and non-traditional families, on the one hand, and a changing labor market, on the other hand, new assertions about their connection have emerged. Using SOEP-data, the possible change in that relationship is investigated in two years, 1986 and 1996. In addition, the influence of success at work and the private life pattern on overall satisfaction with life is analyzed.
Keywords: 330; Lebensqualität; Soziale Mobilität; Arbeitsmarkt; Geschlecht; Deutschland; Ehe